Geographical gradients of dissolved Vitamin B12 in the Mediterranean Sea - Bonnet, Sophie; Tovar-Sanchez, Antonio; Panzeca, Caterina; Ortega-retuerta, Eva; Duarte, Carlos; Sanudo-Wilhelmy, Sergio (Frontiers in Microbiology, 2013)
Most eukaryotic phytoplankton require vitamin B12 to grow. However, the cycling of this organic growth factor has received substantially less attention than other bioactive substances such as trace metals in the marine environment. This is especially true in the Mediterranean Sea, where direct measurements of dissolved vitamins have never been reported. We report here the first direct measurements of dissolved vitamin B12 across longitudinal gradients in Mediterranean waters. The range of vitamin B12 concentrations measured over the whole transect was 0.5 to 6.2 pM, which is slightly higher than the range (undetectable – 4 pM) of ambient concentrations measured in other open ocean basins in the Pacific and Atlantic oceans. The concentrations measured in the western basin were significantly higher (p<0.05) than those of the eastern basin. They were positively correlated with chlorophyll concentrations in the most western part of the basin, and did not show any significant correlation with any other biological variables in other regions of the sampling transect.